1998
DOI: 10.1615/critrevoncog.v9.i1.40
|View full text |Cite
|
Sign up to set email alerts
|

The c-Fes Family of Protein-Tyrosine Kinases

Abstract: The human c-fes protooncogene encodes a protein-tyrosine kinase (c-Fes) distinct from c-Src, c-Abl and other nonreceptor tyrosine kinases. Although originally identified as the cellular homolog of several transforming retroviral oncoproteins, Fes was later found to exhibit strong expression in myeloid hematopoietic cells and to play a direct role in their differentiation. Recent work has shown that Fes exhibits a more widespread expression pattern in both developing and adult tissues, suggesting a general phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 0 publications
0
57
0
Order By: Relevance
“…9 FES and FER (FES-related protein) constitute a distinct sub-family of non-receptor tyrosine kinases. 10 Below, we will refer to FES and FER collectively as FES kinases.…”
Section: Introductionmentioning
confidence: 99%
“…9 FES and FER (FES-related protein) constitute a distinct sub-family of non-receptor tyrosine kinases. 10 Below, we will refer to FES and FER collectively as FES kinases.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that both the coiled-coil domains are necessary for Fes to translocate and that they must be in a specific spatial conformation, since the removal of the portion of p92 cFes between the two coiled-coil domains (D7D11) impairs the translocation. To check whether p92 c-Fes oligomerization (Read et al, 1997;Smithgall et al, 1998;Cheng et al, 1999) is somehow related to the event of nuclear translocation we performed Western blot experiments on HL60 cells overexpressing c-Fes and on K562 cells expressing mutants missing CC1 and CC2. These experiments showed that Fes oligomers are localized in the nucleus and that the deletion of the coiled-coil domains prevents both oligomerization and nuclear translocation, thus confirming the key role of the coiledcoil domains in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that exon 7 encodes a portion of p92 c-Fes located between the two coiled-coil domains, that the process of nuclear translocation probably deals with Fes activation and that evidence exists in literature that CC1 and CC2 are invloved in Fes activation (Read et al, 1997;Cheng et al, 1999;Smithgall et al, 1998), we investigated whether the coiled-coil domains of p92 c-Fes have a role in the process of nuclear translocation. The recombinant constructs encoding the aminoterminal domain of c-Fes and its deleted forms are shown in We treated these cells with the differentiation-inducing agents and checked them at confocal microscopy.…”
Section: Subcellular Localization Of P92 C-fes Nh 2 -Terminal Domain mentioning
confidence: 99%
See 2 more Smart Citations